A new species of Amphicnemis Selys, 1863 from Sumatra, Indonesia and first records of two other species of Amphicnemis for the island (Odonata: Zygoptera: Coenagrionidae) - Dow, Rory A.; Gesriantuti, N.; Lupiyaningdyah, P. (Zootaxa, 2025)
Amphicnemis reri sp. nov. is described from tropical Peat Swamp Forest (PSF) in the Kampar Peninsula, Riau Province, Sumatra, Indonesia (holotype ♂, pools in PSF, Meranti Estate Block B Transect, Kampar Peninsula, Pelalawan, Riau, Sumatra, Indonesia, 0.3363N, 102.6440E, 7 ii 2023, deposited with the Indonesian National Research and Innovation Agency). The female (supposition) is also described. Amphicnemis bebar Dow, Choong & Ng, 2010 and A. hoisen Dow, Choong & Ng, 2010, both originally described from Peninsular Malaysia, are recorded from Sumatra for the first time; variation in these species is discussed and, in the case of A. bebar is illustrated. Species groups within Amphicnemis Selys, 1863 are defined and briefly discussed.